"Wired, " Yet Intoxicated: Modeling Binge Caffeine and Alcohol Co‐Consumption in the Mouse. (24th June 2014) - Fritz, Brandon M.; Companion, Michel; Boehm, Stephen L.
<x xml:space="preserve">Abstract</x> Background The combination of highly caffeinated "energy drinks" with alcohol (ethanol [EtOH]) has become popular among young adults and intoxication via such beverages has been associated with an elevated risk for harmful behaviors. However, there are discrepancies in the human literature regarding the effect of caffeine on alcohol intoxication, perhaps due to confounding factors such as personality type, expectancy, and history of exposure. Animal models of co‐exposure are resistant to such issues; however, the consequences of voluntary co‐consumption have been largely ignored in the animal literature. The primary goal of this work was to characterize a mouse model of binge caffeine and EtOH co‐consumption employing the limited access "Drinking‐in‐the‐Dark" (DID) paradigm. Methods Caffeine was added to a 20% alcohol solution via DID. Alcohol/caffeine intake, locomotor behavior, ataxia, anxiety‐like behavior, and cognitive function were evaluated as a consequence of co‐consumption in adult male C57BL/6J mice. Results Caffeine did not substantially alter binge alcohol intake or resultant blood EtOH concentrations (BECs), nor did it alter alcohol's anxiolytic effects on the elevated plus maze or cognitive‐interfering effects in a novel object‐recognition task. However, no evidence of alcohol‐induced sedation was observed in co‐consumption groups that instead demonstrated a highly stimulated state similar to that of caffeine alone. The addition of caffeine was also found to mitigate alcohol‐induced ataxia. Conclusions Taken together, our mouse model indicates that binge co‐consumption of caffeine and alcohol produces a stimulated, less ataxic and anxious, as well as cognitively altered state; a state that could be of great public health concern. These results appear to resemble the colloquially identified "wide awake drunk" state that individuals seek via consumption of such beverages. This self‐administration model therefore offers the capacity for translationally valid explorations of the neurobiological consequences of binge co‐consumption to assess the public health risk of this drug combination.